PENGARUH METODE DAN WAKI'U PENYULINGAN TERHADAP RENDEMEN DAN SIFAT FISIKO KIMIA MINYAK KENANGA - Bambang Wiyono (Jurnal Penelitian Hasil Hutan, 1990)
This paper  described   the study on  the  effect   of  distilling  time and methods  on yield and pysiocheical properties of  cananga  oil.  The  distillation   methods   applied   were  water  distillation an  water steam  distillation with   the  distilling time  being  8, 16, and  24  hours, consecutively. The  results  were analysed  using  the  randomized completely block  design, and the difference  between means were tested  with  the Least  Significant  Difference  method.The  results  showed that  the  distilling method appeared   to  have  significant   effect   on  the  saponification and ester numbers whereas, the oil yield was  significantly increased  with prolonged distilling time. Water distillation method produced higher quality of  cananga  oil than that produced by  the water-steam distillation  one.  This was indicated  by a higher ester number  of  the oil obtained  by  the water  distillation.